Emergency Remote Teaching in Journalism in the Covid 19 pandemic: an account of the experience of public academy teachers (Comunicação & Inovação, 2021)
The article describes the practice of Emergency Remote Education (ERE) in the Journalism course at a brazilian public university during the Covid-19 pandemic in 2020. The practice of two teachers for the maintenance of teaching and student activities using Information and Communication Technologies (ICTs) as instruments that mediate the teaching-learning practice constitutes the experience report. As a methodological path, the article contextualizes the ERE and discusses the difficulties and strategies implemented for the best didactic-pedagogical use. As a result, weaknesses and potentialities of this experience are pointed out.
Keywords: pandemic; Journalism; Teaching